Myocardial fibrosis in athletes—Current perspective - Małek, Łukasz A.; Bucciarelli‐Ducci, Chiara (Clinical cardiology (Mahwah, N.J.), 2020)
Several previous studies suggested that prolonged and extensive physical activity might lead to increased prevalence of myocardial fibrosis in athletes. The review summarizes these studies focusing on common patterns of myocardial fibrosis observed in athletes, their potential causes and significance. It also presents recent research on parametric imaging shedding new light on diffuse myocardial fibrosis in athletes. Finally, it reviews how these traditional and novel cardiac magnetic resonance (CMR) techniques can be incorporated in the diagnostic work up to differentiate athlete's heart from cardiomyopathies.